The Negative Effects of Workplace Discrimination and Perceived Unfairness on Employee Citizenship Behavior (Journal of Asian Development Studies, 2023)
The paper aims to test the relationship between workplace discrimination on employees and employees' citizenship behavior with the mediating role of perceived unfairness. This research has used a close-ended questionnaire in a survey approach. Middle-level employees from different organizations, including the health, cement, and education sectors, filled out these questionnaires. A total of 300 questionnaires were distributed among employees. Out of them, 203 usable responses were received and analyzed using SPSS and SmartPLS software. Using organizational justice theories, this study has found a positive impact of employee discrimination on perceived unfairness—a negative impact of workplace discrimination on employee's organizational citizenship behavior (OCB). Perceived unfairness also mediated the link between workplace discrimination and OCB. This study suggests that workplace discrimination generates feelings of unfairness and injustice. People may be doing their jobs contained in job descriptions but will not be willing to participate in extra-role behaviors like OCB, which is also essential for organizations. This research paper includes implications for organizational leaders and policymakers and suggests that organizations should treat employees fairly and remove workplace discrimination for positive citizenship behavior.